Factors associated with the outcomes in ulcerative colitis patients undergoing granulocyte and monocyte adsorptive apheresis as remission induction therapy: A multicenter cohort study. Issue 4 (28th November 2020) - Ishiguro, Yoh; Ohmori, Toshihide; Umemura, Ken; Iizuka, Masahiro
Abstract: Ulcerative colitis (UC) patients harbor activated myeloid leukocytes, which exacerbate and perpetuate UC by releasing inflammatory cytokines. Granulocyte and monocyte adsorptive apheresis (GMA) with an Adacolumn depletes elevated myeloid leukocytes, inducing efficacy with favorable safety. To understand how the clinical outcome with GMA is affected by prior corticosteroid treatment or concomitant immunomodulators, a retrospective multicenter study in 102 UC patients, who had not responded well to first‐line medications was undertaken. The remission rates after a course of GMA therapy were significantly higher in corticosteroid‐naïve patients compared with those with prior corticosteroid exposure. Absence of corticosteroid background was an independent predictive factor of response to GMA. Further, in corticosteroid‐naïve patients, the 1‐year cumulative sustained remission rate in patients who did not receive immunomodulators was significantly higher than in patients who received immunomodulators. Accordingly, multivariate analysis revealed that immunomodulator was associated with higher risk of relapse. In conclusion, GMA was an effective treatment for corticosteroid‐naïve patients and the efficacy sustained longer in those not receiving immunomodulators during GMA. GMA fulfills the notion that apheresis is to induce disease remission by removing from the body factors known to perpetuate disease. In therapeutic settings, these findings should help better decision making and avoid futile use of medical resources.